Gambaran Pengetahuan, Sikap Dan Tindakan Pemandu Wisata Dalam Upaya Pencegahan Cacar Monyet (Monkeypox) Di Desa Wisata Liya Togo - Sarni Rahmawati Layn; Hariati Lestari; Febriana Muchtar (KOLONI, 2023)
Monkeypox disease in humans is caused by the monkeypox virus (MPXV) which is a viral infectious disease of the orthopoxvirus genus. In 2022, the prevalence of monkeypox cases has increased rapidly worldwide and the disease has been declared a global public health emergency. In general, monkeypox case detection activities begin with the discovery of suspected/probable/confirmed cases on travelers such as research or foreign tourists. Indonesia as a country with tourism potential has a risk of monkeypox transmission from both local and foreign tourists. Tourist visits are closely related to tour guides who work by meeting various groups and being a group at risk of contracting the disease. The purpose of this study was to see an overview of the knowledge, attitudes and actions of tour guides in efforts to prevent monkeypox in Liya Togo Tourism Village. This type of research is a quantitative descriptive research by conducting surveys about knowledge, attitudes, and actions. The sample for this study was 80 people using a total sample, where all members of the population were respondents. The results of this study indicate that the respondents had good knowledge 35 people (43,7%) and lacked knowledge 45 people (56,3%). The respondents had positive attitudes 74 people (92,5%) and negative attitudes 6 people (7,5%). The respondents exhibited good actions 62 people (77,5%) and inadequate actions 18 people (22,5%). To optimise the knowledge of tour guides, it is expected that related parties can provide guidance to prevent the transmission of monkeypox and other infectious diseases.  Keywords: Knowledge, Attitude, Action, Monkeypox Prevention , Guide Tour